Post-Training Evaluation of Electrical Power Inspectors at PPSDM Kebtke Based on Kirkpatrick Model Level 1 and Level 2 - Didik Hadiyanto; Endan Suwandana (International Journal Labs, 2025)
This study evaluates the effectiveness of a post-training program for electricity inspectors at PPSDM KEBTKE using the Kirkpatrick Evaluation Model (level 1: reaction and level 2: learning) in the Technical Training on Power Plant Inspection for Junior Level. At level 1, participants gave positive feedback, with the training receiving an average score of 89.21, highlighting strengths in content, pre-test/post-test alignment, and participant services. However, scheduling and duration were identified as weaknesses. The Public Satisfaction Index (IKM) showed excellent results with a score of 3.60, particularly in staff behavior, competence, and product specifications. Participants’ reactions toward instructors were also excellent, scoring 90.25, with motivation, material quality, and methods as strengths, though variation in material delivery needs improvement. At level 2, learning outcomes significantly improved, with pre-test and post-test scores showing a t-count of 4.575, greater than the t-table value of 2.01537 at a significance level of 0.05 with 14 degrees of freedom. This result indicates that there is a significant difference in participants' learning outcomes before and after training. In conclusion, the training not only received positive participant feedback but also significantly enhanced their technical competencies. However, improvements in scheduling and instructional methods are recommended to further optimize the training quality.